Case Report: An extremely rare case of epithelioid STUMPs - Li, Danjie; Guan, Yibei; He, Ziqiu; Wang, Yanru; Liu, Xinying; Xiong, Miao; Min, Min (Frontiers in Oncology, 2026)
IntroductionUterine leiomyomas are the most common benign tumors of the female reproductive system. Epithelioid STUMP is a special and relatively rare type of uterine leiomyoma that may exhibit malignant potential as smooth muscle tumors with an epithelioid cell morphology are generally believed to be more aggressive than usual leiomyomas. This report describes a case of epithelioid STUMP.Case descriptionA 45-year-old woman of childbearing age underwent curettage for abnormal uterine bleeding. The initial pathological findings suggested a low-grade malignant uterine mesenchymal tumor; therefore, laparoscopic-assisted vaginal hysterectomy, bilateral adnexal resection, and retroperitoneal lymph node biopsy were performed. Postoperative pathology revealed small, round to short, spindle-shaped tumor cells of uniform size and mild pleomorphism, intermingled with smooth muscle of the uterine wall, with mitotic figures 2-3 per 10 high-power field, suggesting an extremely rare, epithelioid STUMP. The tumor exhibited infiltrative growth at its periphery, indicating malignant potential. The patient did not undergo radiotherapy or chemotherapy postoperatively and the last follow - up after surgery showed that the patient had not recurred for 8 months.ConclusionEpithelioid STUMP, a specific subtype of uterine leiomyomas, may exhibit malignant potential. For this subtype, thorough preoperative examinations (enhanced pelvic magnetic resonance imaging and enhanced abdominal computed tomography) are necessary to avoid misdiagnosis or delayed diagnosis, which can worsen the patient’s condition, and to establish appropriate diagnostic, therapeutic, and prognostic strategies.